Perilaku Pengendara Sepeda Motor Dengan Satu Penumpang dan Lebih dari Satu Penumpang Studi Kasus Pada Mahasiswa di Enam Fakultas UIN Syarif Hidayatullah - Ruthfianiwaty - Ruthfianiwaty; Siti Rahmah Hidayatullah Lubis (Dian Nuswantoro Semarang, 2020)
Riding motorcycle with more than one passenger is a behavior that violates Law Number 22 of 2009 article 106 paragraph 9 and can increase the risk of accidents. Based on the results of a preliminary study of 15 students 10 of them claimed the reason for carrying more than one passenger was because the motorcycle was insufficient and had never received a ban from the security guards.This study uses a qualitative method which aims to describe the behavior between riders with one passenger and riders with more than one passenger reviewed using the theory of planned behavior. Informants were selected by purposive sampling method with a total of 16 informants. Data were collected by using in-depth interviews and observations.Theattitude aspect show that the riders belief that carrying more than one passenger have more disadvantages. In the aspect of subjective norms, riders perceive social pressures obtained from surrounding communities and friends. On the aspects of perceptions of behavioral control that influented the most are the factors that facilitate and inhibit which was the availability of motorcycles.. Riders have a tendency to carry one passenger for fear of being seen as negative, discomfort, and if the motorcycle is sufficient, while riders with more than one passenger behave accordingly if there is a lack of a motorcycle and only for a close distant.Keyword: Carrying more than one passanger, Theory of Planned Behavior, Undergraduate student